Meningkatkan Kesadaran Siswa SMA Sjakhyakirti terhadap Bahaya Bullying : Pendekatan Hukum dan Pendidikan - Surahmi, Mila; Cahyani, Lidya; Erviana, Ria; Amiati, Diah Lara; Saputra, Citra Dewi; Rafie, Patih Ahmad; Waliadin, Waliadin; Irawan, Soni (Universitas Muhammadiyah Mataram, 2026)
Abstract: Bullying is a serious social issue. Although various prevention efforts have been implemented, cases of bullying are still frequently found in many educational institutions. Data collection was conducted on senior high school students at Sjahyakirti High School in Palembang, specifically grades XI and XII. This activity used an educational and participatory approach, with observation methods through counseling activities. The main objective of this study was to educate students to be able to create a safe and bullying-free school environment, while also understanding the legal and educational dimensions in overcoming it. Counseling activities included material presentations, interactive discussions, case simulations, and legal procedure simulations. Through this method, it is hoped that students will be more sensitive and actively contribute to building a culture of mutual respect, thereby reducing bullying incidents. Counseling on the risks of bullying and strategies for overcoming it has proven effective in increasing students' understanding and awareness of the negative consequences of such behavior. Thus, it can be concluded that the integration of educational and legal approaches is very effective in strengthening anti-bullying awareness.Abstrak: Bullying menjadi isu sosial serius, walaupun berbagai upaya Pencegahan telah dilakukan, kasus bullying masih sering ditemui di banyak Lembaga Pendidikan. Pengumpulan data dilakukan pada sisea tingkat menengah atasi di SMA Sjahyakirti Palembang, khususnya kelas XI dan XII. Kegiatan ini menggunakan pendekatan yang bersifat edukatif dan partisipatif, dengan metode observasi melalui kegiatan penyuluhan. Tujuan utama penelitian ini adalah mengedukasi siswa agar mampu menciptakan lingkungan sekolah yang aman dan bebas bullying , sekaligus memahami dimensi hukum dan pendidikan dalam mengatasinya. Kegiatan penyuluhan mencakup pemaparan materi, diskusi interaktif, simulasi kasus, dan simulasi prosedur hukum. Melalui metode ini, diharapkan siswa lebih peka dan aktif berkontribusi dalam membangun budaya saling menghargai, sehingga mengurangi insiden bullying. Penyuluhan tentang resiko bullying serta strategi penanggulangannya terbukti efektif meningkatkan pemahaman dan kesadaran siswa terhadap akibat negative perilaku tersebut. Dengan demikian, dapat disimpulkan bahwa integrasi pendekatan pendidikan dan hukum sangat efektif untuk memperkuat kesadaran anti-bullying.